Largest mucoepidermoid carcinoma of parotid gland in the world - Kumar, Abhishek; Teggimani, Vasant; Hosamani, Ramesh; Chandrapattan, Prathamesh; Koranne, Aboli (International Surgery Journal, 2019)
Mucoepidermoid carcinoma (MEC) is the most common malignant neoplasm of the major salivary glands, accounting for 15.5% of all cases benign and malignant.1 It has multiple types of morphological variants and thus poses a significant challenge in diagnosis on Fine needle aspiration cytology (FNAC). The aim of this article is to report a case of MEC in a 70-years-old male patient who presented with a painless firm fluctuant swelling in left preauricular area on left cheek to Karnataka Institute of Medical Sciences, Hubli. Detailed history was noted, and the swelling was examined clinically. Radiological investigations were carried out. Fine-needle aspiration cytology was done for the lesion and report suggested tumor of the parotid gland. Total parotidectomy procedure was done. There were no intra operative complications and post operatively there was grade 4 Housemann Brackmann facial nerve palsy on left side. The weight of the tumor was 1.45 kg. The histologic picture confirmed that the tumor was MEC of parotid gland. Through this article we want to report the management of giant MEC, the largest to be reported in world literature.